Comparative genomics analysis of pTEM-2262, an MDR plasmid from Citrobacter freundii, harboring two unclassified replicons. (November 2018) - Li, Manli; Li, Fei; Mi, Zhiqiang; Zhao, Yachao; Zhang, Xianglilan; Jiang, Zhaofang; Pei, Guangqian; Zhou, Lijun; Tong, Yigang; Zhao, Baohua
Aim: To genetically characterize the multidrug-resistance (MDR) plasmid pTEM-2262 that could not be classified into any known incompatibility group from the clinical Citrobacter freundii isolate 2262.Materials & methods: The repA or repB deletion mutants of pTEM-2262 were constructed using the scarless Cas9-assisted recombineering system. Comparative genomic analysis of pTEM-2262 and the other four previously sequenced plasmids belonging to the same incompatibility group were performed.Results: pTEM-2262, a conjugative plasmid, harbored two unclassified replicons, repA and repB, while repB was not essential for pTEM-2262 replication. In five analyzed plasmids, their conserved backbones primarily integrated massive accessory modules at two 'hotspots' that were located between orf597 and orf504, and between orf393 and orf405 . All the antibiotic resistance genes of pTEM-2262 were clustered in the MDR region with a complex mosaic structure.Conclusion: This study thoroughly investigates the detailed structure and genomic comparison of this unknown incompatibility group for the first time.